Carotenoids purification from gac (Momordica cochinchinensis Spreng.) fruit oil. (March 2016) - Mai, H.C.; Truong, V.; Debaste, F.
Abstract: A process to isolate and purify carotenoids for gac ( Momordica cochinchinensis Spreng.) fruit oil is presented and optimized. Carotenoids were purified and isolated by a saponification and using propylene glycol. A two steps experimental procedure was followed to optimize the process. In the first step, an evaluation of the impact of the different parameters one by one was realized. Results indicate that using Tween 80 (from 0.01 to 0.05 mL/g oil) can help increasing carotenoids recovery. Combination of 0.4 mL/g oil of potassium hydroxide and 0.8 mL/g oil of propylene glycol lead to a maximum carotenoids recovery. Three parameters (stirring speed, temperature and time of reaction) were studied in a central composite design of experiments. Optimal conditions were estimated using a second order Response Surface Methodology. In the optimal conditions (1094 rpm of stirring speed, 46 °C of temperature and 228 min of reaction time), the estimated yield would be around 93%. Highlights: First ever publication of lycopene crystallisation from gac fruit with green solvent. Process based on green, GRAS and low cost materials. High yield of lycopene recovery achieved, opening possibilities of further purification. Optimized yield could reach 93%.